Physical strength of mortar with treated crumb rubber as partial replacement for fine aggregate - ABDUL RANI, FARID AZRI; Musa, Mohd Kamaruzaman; Supar, Khairi (Progress in Engineering Application and Technology, 2022)
Mortar offers great opportunity to replace ingredients like fine aggregate with tyre rubber waste in the form of crumb. It offers great environmental and technical benefits in terms of sustainable concrete production. The lack of bonding between crumb rubber and cement paste can be overcome by treating crumb rubber with sodium hydroxide. The objective of this study is to identify the used of crumb rubber in mortar, determine the optimal percentages of crumb rubber in mortar, and investigating the effect of the sodium hydroxide (NaOH) crumb rubber treatment on mortar mechanical strength and physical strength. This paper using a mix proportion of 1:4 and water-cement ratio of 0.50. Five different percentages (0, 3, 6, 9, and 12%) of fine aggregate replacement were investigated. The mortar compressive strength, density, and water absorption were evaluated after 7 days and 14 days. The compressive value for mortar with 3% crumb rubber show the highest value 21.63 MPa after 14 days compare to the other replacement ratio. Density for mortar cube show a decrement when percentage of treated crumb rubber is increased. For the mortar water absorption, the highest percentage is at 12% crumb rubber replacement which is 11.76% and it found that the water absorption is increased with increasing of crumb rubber percentage.